Basics in Magnetic Resonance guided Focused Ultrasound: technical basis and clinical application. A brief overview - Palumbo, Pierpaolo; Daffinà, Julia; Bruno, Federico; Arrigoni, Francesco; Splendiani, Alessandra; Di Cesare, Ernesto; Barile, Antonio; Masciocchi, Carlo (Acta Biomedica Atenei Parmensis, 2021)
First applications of high focused ultrasound as intracranial ablative therapy were firstly described in early 50’. Since then, the technological innovations have shown an increasingly safe and effective face of this technique. And in the last few years, Magnetic Resonance (MR) guided Focused Ultrasound (gFUS) has become a valid minimally invasive technique in the treatment of several diseases, from bone tumors to symptomatic uterine fibroids or essential tremors.MR guidance, through the tomographic view, offers the advantage of an accurate target detection and treatment planning. Moreover, real-time monitoring sequences allow to avoid non-target ablation.An adequate knowledge of FUS is essential to understand its clinical effectiveness. Therefore, this brief review aims to debate the physical characteristics of US and the main fields of clinical application.